Modified pegRNAs mitigate scaffold-derived prime editing by-products - Panagiotis Antoniou; Louis Dacquay; Hanna Mårtensson; Katja Madeyski-Bengtson; Anna-Lena Loyd; Anna Shiriaeva; Euan Gordon; Salman Mustfa; George Thom; Pei-Pei Hsieh; Saša Šviković; Mike Firth; et al. (Nature Communications)
Abstract Prime editors (PEs) employ reverse transcriptase (RT) to install genomic edits using a template within the prime editing guide RNA (pegRNA). RT creates a 3’ genomic flap containing the intended edit. However, reverse transcription can continue beyond the template, incorporating the pegRNA scaffold sequence into the 3’ flap. These scaffold-derived by-products can be installed alongside the intended edit, reducing prime editing precision. Here, we develop a method that prevents RT from accessing the scaffold, thereby mitigating such by-products. We demonstrate that an internal abasic spacer or 2’-O-methylation within the pegRNAs terminates RT at the end of the template. This prevents scaffold-derived sequences from being incorporated into the target locus. We benchmark these pegRNAs in different cell types and demonstrate that they can be used with processive PEs such as PE6d or PE**. Our findings provide a simple approach to mitigate a common prime editing by-product and improve prime editing precision.